Effect of Some Essential Oils on in vitro Ruminal Fermentation of Alfalfa Hay - Önel, Süleyman Ercüment; Aksu, Taylan; Kalamak, Adem; Kaya, Durmuş Alpaslan; Aksu, Devrim Sarıpınar; Sakin, Fatih; Türkmen, Musa (Progress in Nutrition, 2021)
Study Objectives: This study aimed to investigate the effects of essential oils derived from the leaves of Laurus nobilis (LNEO), Myrtus communis (MCEO), Lavandula stoechas (LSEO), Artemisia annua (AAEO), and Thymbra spicata (TSEO) on the rumen fermentation parameters (gas production, methane emission, organic acids, and the number of protozoa) of dry alfalfa hay. Methods: The components of all essential oils were analyzed. The effects of adding the same dose (60 mg/L) of each essential oil to the rumen fluid on in vitro rumen digestion were determined by in vitro gas production. Results: The addition of Lavandula stoechas, Artemisia annua, Myrtus communis, and Laura nobilis essential oils decreased the total gas and methane formation (ml), organic matter digestion (OMD), ruminal ammonia nitrogen levels, and the metabolic energy (ME) values. On the other hand, the Thymbra spicata essential oil did not affect any parameter except the ruminal ammonia nitrogen level. The rumen protozoa numbers were unaffected by the addition of Thymbra spicata essential oil. The total volatile fatty acids (TVFA), acetic acid (AA), propionic acid (PA), and butyric acid (BA) amounts in the in vitro fermentation fluid of alfalfa hay were low in all groups. Conclusion: It was determined that the active ingredients of LSEO, AAEO, MCEO, and LNEO may have a regulatory effect on ruminal fermentation. We think that more studies using different feed types and combinations of essential oils are required to reveal the effects of these essential oils on ecology and the physiology of the digestive system.